A Review of the Teratogenic Factors Effect on Embryo - Manzarbanoo Shojaei fard; Samira Malekzadeh; Mehrdad Shariati (Journal of Advanced Biomedical Sciences, 2016)
Background & Objectives: Teratology is a branch of embryology science that studies causes, mechanisms and abnormal pattern development. Embryo growth traumatic factors during pregnancy are called teratogens that some teratogens pass the placental barrier and cause adverse effect during development stages and malformation, however a drug may improve general health of the mother, but it might be poisonous for embryo and cause diverse malformation. Since study of embryo health and risk factor in this stage is important, the aim of this review article was the investigation of some types of teratosgens (such as radiation, infectious agents, heat disorders, maternal conditions) and particularly the effect of teratogenic drugs on embryo including some legal drugs (such as acetaminophen, thalidomide, acyclovir, sedatives and anticonvulsants) and illegal drugs (such as nicotine, alcohol, cocaine and marijuana).